THE ROLE OF E-LEARNING INFRASTRUCTURE AND COGNITIVE COMPETENCE IN DISTANCE LEARNING EFFECTIVENESS DURING THE COVID-19 PANDEMIC - Garad, Askar; Al-Ansi, Abdullah M.; Qamari, Ika Nurul (Cakrawala pendidikan : CP, 2021)
Covid-19 has led to the closure of educational institutions around the world and turned formal learning into distance learning. This study aims to investigate the effect of e-learning infrastructure and individual's knowledge and competence on distance learning during the Covid-19 pandemic outbreak in 2020. E-learning infrastructure and individual's cognitive competence were also used to determine the readiness of educational institutions in distance learning. The e-learning infrastructure includes Learning Management System (LMS), electronic devices, communication applications, and internet accessibility. Quantitative approach was used in this study with a sample of 324 participants from three major universities in Yogyakarta, Indonesia. Data were collected through online surveys. The descriptive statistical approach and one-layer regression analysis were used to examine the problems raised in this study. The results show that distance learning is positively influenced by e-learning infrastructure and the cognitive competence of the students, the faculty, and administrative staff. The results also point out the university's readiness level in adopting online learning based on their previous experience of using the learning system. Finally, the study proposes that in order to improve the e-learning process, there needs to be sufficient financial support from the government, whereas the universities are advised to conduct workshops and training, and to provide teleconferencing applications.